2021
DOI: 10.1002/brb3.2238
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification of autism spectrum disorder in children using cortical thickness and support vector machine

Abstract: Objective: Autism spectrum disorder (ASD) is a neurodevelopmental condition with a heterogeneous phenotype. The role of biomarkers in ASD diagnosis has been highlighted; cortical thickness has proved to be involved in the etiopathogenesis of ASD core symptoms. We apply support vector machine, a supervised machine learning method, in order to identify specific cortical thickness alterations in ASD subjects.Methods: A sample of 76 subjects (9.5 ± 3.4 years old) has been selected, 40 diagnosed with ASD and 36 typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…But Squarcina et al found that CT increased in various brain regions in ASD subjects, confirming their role in the pathogenesis of this condition. Considering the brain development curve during ages, these changes in CT may normalize during development [46].…”
Section: Discussionmentioning
confidence: 99%
“…But Squarcina et al found that CT increased in various brain regions in ASD subjects, confirming their role in the pathogenesis of this condition. Considering the brain development curve during ages, these changes in CT may normalize during development [46].…”
Section: Discussionmentioning
confidence: 99%
“…Existing methodologies for reducing the dimensionality of features include feature extraction, feature selection, and sparse learning methods. F-score ( Devika and Oruganti, 2020 ; Fu et al, 2021 ), Recursive Feature Elimination ( Ali et al, 2021 ; Fu et al, 2021 ), PCA ( Irimia et al, 2018 ), greedy selection ( Squarcina et al, 2021 ), and AEs ( Sen et al, 2018 ) are examples of feature selection techniques.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Several researchers have developed ML algorithms employing sMRI ( Moradi et al, 2017 ) or multimodal data ( Eill et al, 2019 ) to diagnose ASD or uncover novel biomarkers for it ( Table 2 , summarizing all ML-based studies). SVM has been extensively evaluated, with ACCs ranging from 45 to 94% on various ASD datasets ( Morris and Rekik, 2017 ; Squarcina et al, 2021 ). In addition, various additional conventional ML models, such as NB ( Xiao et al, 2017 ), KNN ( Yassin et al, 2020 ), AdaBoost ( Bilgen et al, 2020 ), and RF ( Devika and Oruganti, 2020 ), have been examined.…”
Section: Highlighted Researchmentioning
confidence: 99%
“…Conventional method: The most popular is the SVM. It is in many neuroimaging tasks Chen et al [2016], Squarcina et al [2021], Jahedi [2020]. However, SVM is not recommended when the samples less than the features number due to the overfitting.…”
Section: Statistical Analysis and Classification Modelsmentioning
confidence: 99%